Evaluasi Layanan BPJSTK Mobile Dengan Menggunakan Domain Deliver, Service and Support Berdasarkan Framework COBIT 5 (Studi Kasus : BPJS Ketenagakerjaan Cabang Mataram) - Ulfatisa Cahyani; Ismiarta Aknuranda; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
BPJS (Social Assurance Administering Institution) Employment is a public program that provides labor protection. In the implementation of its duties BPJS Employment applying information technology as one of support for achieving business goals one of them is by developing BPJSTK Mobile service. BPJSTK Mobile is a service application for participants as a form of expansion of the information service media presented to workers who want to ensure the fulfillment of their rights by the company. The importance of BPJSTK Mobile service to perform operational activities should be optimal, but the lack of governance in the application of information technology resulted in less optimal company in carrying out the task and achievement of goals, so that BPJSTK Mobile needs to be evaluated so that companies can measure whether the information technology implemented is appropriate with the expected. In this research, the information technology governance standard used is COBIT 5 with the Deliver, Support, Services (DSS) domain. The result of this research shows that the Capability Level of DSS01 and DSS02 process are at level 2, that are managed process. DSS03, DSS04, DSS05 and DSS06 process are at the 1st level performed process. Recommendations are to improve business process activities by optimally utilizing the application and create a complete Standard Operational Procedure (SOP) related to enterprise information technology.